Development and validation of meaningful hybrid e-training model for computer education - Din, Rosseni; Nordin, Mohamad Sahari; Abu Kassim, Noor Lide; Tunku Ahmad, Tunku Badariah; Jusoff, Kamaruzzaman; Johar, Nur Ayu; Kamarul Zaman, Muhammad Faizal; Zakaria, Mohamad Shanudin; Ahmad, Mazalah; Abdul Karim, Aidah; Mastor, Khairul Anwar (Tech Science Publications, 2010)
Meaningful hybrid e-training experience provides a coherent purpose for strategic educational change through lifelong education and the creation of a knowledge society. A close examination of new hybrid e-training programs however, has indicated a critical gap between rapidly developing technology and sound pedagogical models to determine program quality. Therefore, the objective of this study is to develop, generate, test and validate a 2 stage model for a new meaningful hybrid e-training program. The early framework of the model guided development of a questionnaire to measure meaningfulness of a hybrid e-training. Data collected from 213 ICT trainers were tested with confirmatory factor analysis using AMOS 7.0 to obtain three best-fit measurement models from the three latent variables. Overall reliability analyses using Cronbach’s Alpha, items and persons reliability using the Rasch Model and content validation by experts suggested that the questionnaire is reliable and valid to measure a meaningful hybrid e-training program. Subsequently, the structural equation modeling was applied to test the hypotheses. The results showed that there is a positive strong relationship between hybrid e-training and meaningful e-training; a positive weak relationship between learning style preference and hybrid e-training and a negative relationship between learning style preference and meaningful learning. In brief the study showed a substantial effect of hybrid e-training towards achieving meaningful learning. As such, future training regarding the use of hybrid e-training should include all five components of a meaningful hybrid e-training instead of merely focusing on content. With results showing weak relationship between learning style and hybrid etraining and negative relationship between learning style and meaningful e-training, instructional media designers and developers should now focus on integrating all five etraining components to ensure meaningful learning. It would be interesting to further investigate as to whether or not learning style is a mediating or a moderating factor towards achieving meaningful learning via the use of hybrid e-training programs as modeled in the final results.